IDENTIFIKASI FENOTIP JENIS JENIS TANAMAN LIDAH BUAYA (Aloe Sp.) DI DAERAH ISTIMEWA YOGYAKARTA - Maria Theresia Darini (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2018)
The study aims to determine the types, population, frequency and dominance Aloe Sp. plant has been conducted in Yogyakarta, from March to September 2012. Research carried out by the method of vegetation analysis through surveys and sampling of the Aloe Sp. plant locations, districts in the regency in the province of Yogyakarta Special Teritorial. To determine the types of Aloe Sp. plants using descriptions that are tailored to the identification of key observations dichotomi.Variabel method includes types - types of plants, frequency distribution, and plant dominance. Analysis of variance real level of 5%, in order to know the real difference between the district / sub-district results showed that in Yogyakarta found three (3) types of plants are: Aloe ferox Mill, Aloe vera L. and Aloe barbadensis. Highest population in both counties is Aloe vera and province. While the lowest population is Aloe barbedensis . Frequency spread between the types of Aloe vera L.and Aloe ferox Mill equal 100%, while Aloe barbadensis least 80%. Highest dominance of this type of Aloe vera L.